Influence of rotor endcaps on the electromagnetic performance of high speed PM machine - Al-Timimy, Ahmed; Alani, Mahir; Degano, Michele; Giangrande, Paolo; Galea, Michael; Gerada, Christopher (Institution of Engineering and Technology, 2018)
Surface-mounted permanent magnet (SPM) machines are preferred for high-speed aerospace applications over induction and switched reluctance machines, since they combine the advantages of high torque density and efficiency. Also, in aerospace applications, where low rotor weight and inertia are essential requirements, a permeable hollow shaft is proposed to replace the need for rotor back-iron and reduce the overall rotor weight. For rotor mechanical integrity, a retaining sleeve is commonly used, leading to thicker magnetic airgap. Furthermore, when permeable rotor endcaps are applied, an increase of the magnetic end leakage occurs, i.e. end-effect. In this paper, the influence of the rotor endcaps on the mechanical and electromagnetic performance of a high-speed SPM machine is investigated through 3D-finite element analyses (FEA). Also, different endcap thickness and different rotor shaft materials are investigated and compared in this work. Finally, a prototype of the SPM machine under study has been manufactured and tested. The comparison between simulation and experimental results is presented and discussed.